Daniel Deronda - Eliot, George, 1819-1880. ([Auckland, N.Z.] : Floating Press, 2009)
Deronda, a high-minded young man searching for his path in life, finds himself drawn by a series of dramatic encounters into two contrasting worlds: the English country-house life of Gwendolen Harleth, a high-spirited beauty trapped in an oppressive marriage, and the very different lives of a poor Jewish girl, Mirah, and her family. As Deronda uncovers the long-hidden secret of his own parentage, Eliot's moving and suspenseful narrative opens up a world of Jewish experience previously unknown to the Victorian novel.
Archived by the National Library of New Zealand.
Title from PDF title page (viewed on May 31, 2011).
"First published in 1876"--Page 2
Hypertext links contained in the archived instances of this title are non-functional.
eBooks on EBSCOhost
Keywords: Jews -- England -- Fiction; Zionists -- Fiction; England -- Fiction; Angleterre -- Romans, nouvelles, etc; FICTION -- General; Jews; Zionists; England; Fiction